2012
DOI: 10.1111/j.1479-8301.2012.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional dependence and caregiver burden in Alzheimer's disease: a controlled trial on the benefits of motor intervention

Abstract: Background: Cognitive decline has a negative impact on functional activities in Alzheimer's disease. Investigating the effects of motor intervention with the intent to reduce the decline in functionality is an expected target for patients and caregivers. The aim of this study was to verify if a 6-month motor intervention programme promoted functionality in Alzheimer's patients and attenuated caregivers' burden. Methods: The sample comprised 32 community patients with Alzheimer's disease and their 32 respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 36 publications
1
51
1
4
Order By: Relevance
“…As with HRQOL, our study is the first to report the burden for caregivers of FXS patients through the Zarit Burden Interview, and we found the score to be significantly higher than any Zarit burden measure reported for other diseases with relatively comparable functional impairment in the three countries for which we had data. The highest score reported in the literature was 35.6 and was measured in caregivers of patients with Alzheimer's disease in Brazil [52], while a recent study found a mean score of 29.3 in Japanese mothers of children with intellectual disability [53]. In addition, the substantial burden documented here is consistent with a study reporting that a considerable proportion of caregivers were injured in the past year by their child with FXS [10].…”
Section: Discussionsupporting
confidence: 88%
“…As with HRQOL, our study is the first to report the burden for caregivers of FXS patients through the Zarit Burden Interview, and we found the score to be significantly higher than any Zarit burden measure reported for other diseases with relatively comparable functional impairment in the three countries for which we had data. The highest score reported in the literature was 35.6 and was measured in caregivers of patients with Alzheimer's disease in Brazil [52], while a recent study found a mean score of 29.3 in Japanese mothers of children with intellectual disability [53]. In addition, the substantial burden documented here is consistent with a study reporting that a considerable proportion of caregivers were injured in the past year by their child with FXS [10].…”
Section: Discussionsupporting
confidence: 88%
“…The search strategy led to four controlled trials investigating the effect of a dyadic exercise intervention including both the persons with dementia due to AD and the caregivers (Canonici et al, 2012; Lowery et al, 2014; Pitkala et al, 2013; Prick, de Lange, Twisk, & Pot, 2015). We also included secondary analyses of the Pitkala et al study (Öhman et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…All the studies evaluated a dyadic exercise intervention against a no-exercise control group (usual care; Canonici et al, 2012; Lowery et al, 2014; Öhman et al, 2016; Pitkala et al, 2013; Prick et al, 2015). One study also compared two different types of intervention: customized home-based exercise and group-based exercise (Pitkala et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] Para o tratamento, indica-se terapia farmacológica, mas também a não farmacológica, que pode incluir: estimulação cognitiva, convívio social 6,7 e prática regular de atividade física. 8 A literatura científica tem mostrado que, de uma forma geral, a prática regular de atividade física é capaz de proporcionar benefícios cognitivos, comportamentais e funcionais, [9][10][11] além de contribuir para um bom desempenho nas atividades de vida diária. 12 Nota-se, no entanto, que a maioria das estratégias não farmacológicas, sobretudo a intervenção motora, em geral são desenvolvidas em clínicas ou universidades, o que pode dificultar o acesso ao tratamento, principalmente para aqueles que se encontram no estágio avançado da doença, por apresentarem maior comprometimento cognitivo e motor e, consequentemente, maior dificuldade de acesso a tratamentos fora de seu domicílio.…”
Section: Introductionunclassified